Implementation and evaluation of virtual multiple mini interviews as a selection tool for entry into paediatric postgraduate training: A Queensland experience. (2nd January 2022) - Sabesan, Vanaja; Kapur, Nitin; Zemanek, Kylie; Levitt, David; Vu, Tung; Van Erp, Ansmarie
Abstract: Introduction: The Queensland Basic Paediatric Training Network (QBPTN) is the centralised pathway for entry into paediatric training in Queensland, Australia. In response to COVID-19 travel and social distancing restrictions imposed in 2020, QBPTN successfully adopted a Virtual Multiple Mini Interviews (vMMIs) model for the selection of candidates for entry into paediatric training. The authors describe the planning, implementation, challenges, and evaluation of candidates' and interviewers' experiences of vMMIs, including the differences between candidates from two geographical areas. Methods: The contents of six vMMI stations were similar to face-to-face MMI. Implementation required the identification of ZOOM TM as a preferred online platform, securing venues, communication, development of contingency plans and central coordination by the network. Candidates' experiences with vMMI were explored through thematic analysis of the qualitative data from focus groups and free text responses, and descriptive analysis of SurveyMonkey© questionnaire responses. Experiences between 'metropolitan' and 'regional and interstate' candidates were compared. Results: 5-minute stations with 2-minute pre-reading were used. 78 candidates and 14 interviewers participated in the selection process. All candidates attended the focus group. 58.7% of candidates responded to post vMMI questionnaire. 93% of survey responders were happy to undertake vMMI in the future, with 23% feeling they would have performed better in face-to-face. Experiences between 'metropolitan' and 'other' groups were similar. Positive experiences of participants were related to the user-friendly IT platform, successful pre-interview communications, preparation, convenience, time, and cost savings. Stress related IT failures and difficulties establishing rapport with interviewers were reported as the main negative experiences. Conclusion: 'vMMI' is a feasible and acceptable method of selection into paediatric training. vMMI has many benefits and can be implemented relatively quickly by addressing key logistical requirements. The model under discussion could be adapted by other centres based on local needs.